(untitled) (Iranian Journal of Kidney Diseases, 2014)
Introduction. We aimed to identify immune status of the stable kidney allografts from the point of some cellular changes that may occur after transplantation. Materials and Methods. This study considered 57 patients with no rejection during the 6 months after transplantation. Flow cytometric frequencies of circulatory CD4+CD25+FoxP3+ and CD8+CD28- regulatory T cells (Treg) as well as myeloid dendritic cells type 1 (MDC1) and type 2 (MDC2) and plasmacytoid dendritic cells (PDC) were measured before transplantation and 2 weeks and 1, 3, and 6 months after transplantation. Using adjusted model of repeated measure analysis, we assessed the influence of different parameters on different cell subsets. Results. The mean number of Tregs and PDCs decreased 2 weeks after transplantation and then increased as they reached their values before transplantation within a few months after transplantation. The mean MDC1s increased during 2 weeks and then decreased to its before-transplantation values within 6 months. The frequency of Tregs (r = 0.90) and MDC1s (r = 0.75) at month 3 could strongly predict their frequencies at month 6. Different variables including family relationship between donor and recipient, glomerular filtration rate, and human leukocyte antigen antibody mismatch did not change the frequency of different cell subsets during the time. Conclusions. The dynamism and circulatory changes in the frequency of Tregs and PDCs are opposite to MDCs after kidney transplantation. We describe these changes in a group of patients with stable graft; however, our study does not render any idea in patients with unstable or rejecting grafts.